Metabolic and Evolutionary Insights in the Transformation of Diphenylamine by a Pseudomonas putida Strain Unravelled by Genomic, Proteomic, and Transcription Analysis - Papadopoulou, Evangelia S.; Perruchon, Chiara; Vasileiadis, Sotirios; Rousidou, Constantina; Tanou, Georgia; Samiotaki, Martina; Molassiotis, Athanassios; Karpouzas, Dimitrios G. (Frontiers in Microbiology, 2018)
Diphenylamine (DPA) is a common soil and water contaminant. A Pseudomonas putida strain, recently isolated from a wastewater disposal site, was efficient in degrading DPA. Thorough knowledge of the metabolic capacity, genetic stability and physiology of bacteria during biodegradation of pollutants is essential for their future industrial exploitation. We employed genomic, proteomic, transcription analyses and plasmid curing to (i) identify the genetic network of P. putida driving the microbial transformation of DPA and explore its evolution and origin and (ii) investigate the physiological response of bacterial cells during degradation of DPA. Genomic analysis identified (i) two operons encoding a biphenyl (bph) and an aniline (tdn) dioxygenase, both flanked by transposases and (ii) two operons and several scattered genes encoding the ortho-cleavage of catechol. Proteomics identified 11 putative catabolic proteins, all but BphA1 up-regulated in DPA- and aniline-growing cells, and showed that the bacterium mobilized cellular mechanisms to cope with oxidative stress, probably induced by DPA and its derivatives. Transcription analysis verified the role of the selected genes/operons in the metabolic pathway: DPA was initially transformed to aniline and catechol by a biphenyl dioxygenase (DPA-dioxygenase); aniline was then transformed to catechol which was further metabolized via the ortho-cleavage pathway. Plasmid curing of P. putida resulted in loss of the DPA and aniline dioxygenase genes and the corresponding degradation capacities. Overall our findings provide novel insights into the evolution of the DPA degradation pathway and suggests that the degradation capacity of P. putida was acquired through recruitment of the bph and tdn operons via horizontal gene transfer.